Using Pseudo-panels to Measure Income Mobility in Latin America - Cuesta, Jose; Nopo, Hugo; Pizzolitto, Georgina (2012)
This paper presents a comparative overview of mobility patterns in 14 Latin American countries between 1992 and 2003. Using three alternative econometric techniques on constructed pseudo-panels, the paper provides a set of estimators for the traditional notion of income mobility as well as for mobility around extreme and moderate poverty lines. The estimates suggest very high levels of time-dependent unconditional immobility for the region. However, the introduction of socioeconomic and personal factors reduces the estimate of income immobility by around 30 percent. There are also large variations in country-specific income mobility (estimated to explain some additional 10 percent of inter-temporal income variation). Analyzing the determinants of changes in poverty incidence within cohorts revealed statistically significant roles for age, gender, and education of the household head, the latter subject to distinctive effects across levels of attainment and transition in and out of poverty.